Modeling of fluid flow inside UMP's francis turbine using computational fluid dynamics (CFD) - Muhammad Nur Iznei, Hashim (2009)
This project describes and explains the fluid flow conditions and parameters within a Francis Turbine with regards to each part of the turbine in contact with the working fluid and all working parts of the turbine. The process of obtaining the fluid flow condition and characteristic within the turbine is done by Computational Fluid Dynamics (CFD) simulation. Before CFD simulation is done, a model of the Francis needs to be selected as there are wide ranges of model ranging from conventional usage to demonstration purposes. Considering the availability of the turbine and data, UMP’s Gunt Hamburg Demonstration Francis Turbine HM150.20 was selected. The project was then continued by referring to this model. The project was divided into 3 main parts that is experiment on the actual Francis Turbine in order to get real data which will then be used to validate the simulation data by the mean of comparing efficiency curve. The next part is Computer Aided Design (CAD) modeling based on the Gunt Hamburg Demonstration Francis Turbine HM150.20 dimensions and specifications obtained from the manufacturer and measurement on the actual turbine. The CAD modeling was done with consideration to the working parts of the turbine and external parts which are not bounded by the fluid flow region are placed with equivalent readout such as torque which is measured directly at the runner. The third part of the project would be the simulation by using CFD code. During this part, the constructed CAD model is subjected to boundary and flow conditions obtained from experiment and run to obtain the required data. After simulation is done by CFD code, the data obtained is validated by comparing the efficiency curve to verify that the simulation result is correct and fulfill the condition needed for analysis. The significance of the project is that it provides comprehensive and complete flow condition within UMP’s Gunt Hamburg Demonstration Francis Turbine HM150.20 which can be used for further studies on the fluid flow inside the turbine and efficiency improvement for the turbine.